LEGAL POLITICS OF REVOKING THE EXTRAORDINARY CRIME STATUS OF CORRUPTION CRIMINAL ACT THROUGH THE NEW KUHP AND ITS IMPLICATIONS FOR THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Amlan, Amlan; T Riza Zarzani; Henry Aspan (International Journal of Synergy in Law, Criminal, and Justice, 2024)
After independence, the Indonesian Criminal Code (KUHP) was implemented nationwide through Law No. 73 of 1958, ending legal dualism in Indonesia. In 1971, anti-corruption efforts were formalized through Law No. 3 of 1971, later updated by Law No. 31 of 1999 and Law no. 20 of 2001. These changes introduced the principle of reverse burden of evidence and severe sanctions for corruption offenders. Subsequent Constitutional Court decisions reinforced the legality of corruption cases by restricting criminal acts to explicitly defined legal actions. However, the removal of the extraordinary crime status for corruption under Law No. 1 of 2023 raises concerns over the reduced deterrent effect and the weakening of the KPK's authority. Comprehensive reform is needed to ensure anti-corruption enforcement remains grounded in Pancasila and the Constitution.